2012
DOI: 10.1210/me.2012-1075
|View full text |Cite
|
Sign up to set email alerts
|

miR-93/106b and Their Host Gene, MCM7, Are Differentially Expressed in Leiomyomas and Functionally Target F3 and IL-8

Abstract: miR-93/106b and their host gene minichromosome maintenance complex component 7 (MCM7) reside at chr7q22, a region frequently rearranged in leiomyomas. We explored the expression of miR-93/106b in leiomyoma and paired myometrium (n = 63) from untreated and patients exposed to hormonal therapies (GnRH agonist, Depo-Provera, and oral contraceptives) from African-Americans and Caucasians and their regulatory functions in isolated paired (n = 15) leiomyoma and myometrial smooth muscle cells and the leiomyosarcoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 62 publications
4
94
0
1
Order By: Relevance
“…Among the microRNAs, miR-93-5p is clearly demonstrated in a variety of cellular systems to be involved in post-transcriptional regulation of IL-8 and VEGF gene expression (15,(29)(30)(31). For instance, we found that the effects of bacterial challenge activating IL-8 gene transcription in epithelial cells are downregulated by miR-93-5p (29).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Among the microRNAs, miR-93-5p is clearly demonstrated in a variety of cellular systems to be involved in post-transcriptional regulation of IL-8 and VEGF gene expression (15,(29)(30)(31). For instance, we found that the effects of bacterial challenge activating IL-8 gene transcription in epithelial cells are downregulated by miR-93-5p (29).…”
Section: Introductionmentioning
confidence: 81%
“…As expected, one of the control levels is transcription-related to the interaction between IL-8 and VEGF promoters and different transcription factors, such as NF-κB, AP-1 and C-EBP/NF-IL-6 (7)(8)(9)(10)(11)(12). In addition, the expression of IL-8 and VEGF genes may be under the control of epigenetic mechanisms, such as those regulated by microRNAs in cancer, differentiation and inflammatory processes (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The mir106b cluster is embedded within the MCM7 gene, which is a direct RB/E2F target gene. 16,[26][27][28][29][30] The mir106b cluster targets the expression of several genes that are directly disease-relevant and that provide a mechanism for cross-talk from the canonical RB pathway to PTEN and p21…”
Section: Discussionmentioning
confidence: 99%
“…HU et al [12] have demonstrated that IL-8 is susceptible to modulation by miR-520b in breast cancer cells, while YU et al [13] have shown that the miR-17/20 cluster regulates the IL-8 3′UTR. Other studies have reported that miR-203 and miR-93/106b regulate IL-8 expression [14,15]. BHATTACHARYYA et al [16] reported how increased levels of miR-155 indirectly elevate IL-8 in CF IB3 cells, CF bronchial brushings and CF neutrophils.…”
Section: Introductionmentioning
confidence: 99%